Activity of Phosphites and Chitosan on Biochemical Responses and Target Spot Control in Cucumber Plants - Fischer, Ivan Herman; Morales, João Vitor Pelizzaro; da Silva, Lucas Meleiro; de Almeida Bertani, Rosemary Marques; Deus, Angélica Cristina Fernandes [UNESP]; Pascholati, Sérgio Florentino (Springer Nature, 2022)
Target spot, a disease caused by Corynespora cassiicola, is a frequent disease in the cucumber crop but still without an effective control. The objective was to evaluate the effect of phosphites and chitosan on the in vitro control of C. cassiicola and target spot in a greenhouse by characterizing the biochemical responses of treated plants inoculated with such a pathogen. Three weekly sprayings with phosphites (1 mL L−1) and chitosan (1 g L−1) were carried out, and the pathogen was inoculated in two true leaves after four days of the last spraying. Manganese, zinc, magnesium, potassium and copper phosphites inhibited C. cassiicola mycelial growth (> 80%) and germination (> 11%). Zinc phosphite was most efficient in controlling the disease, reducing the severity by 79%, and was followed by manganese, copper and potassium phosphites. Zinc and manganese phosphites reduced the number of lesions on the leaves. Except for magnesium phosphite, the applied products reduced the diameter of lesions after ten days of the pathogen inoculation. The products did not affect pathogen sporulation on the leaves. The enzyme peroxidase was induced by copper phosphite; polyphenol oxidase increased with zinc, manganese, copper and magnesium phosphites, and the levels of free phenolic compounds were higher with copper phosphite. Considering the present results for target spot control, copper, zinc and manganese phosphites can be associated with antifungal activity and plant resistance induction, while for potassium phosphite, antifungal activity was apparently more important to control the disease.
Keywords: Alternative control; Corynespora cassiicola; Cucumis sativus; Resistance induction